Vulnerabilidades de los riesgos en el tráfico de la red informática del Infocentro de la Parroquia "Guare" - Mosquera Sánchez, Herlinda Narcisa (2019)
The community Infocentros belong to a project destined to the rural area of ​​Ecuador, with the objective that the society where they are has access to computer services, internet and training courses for free, managed by the Ministry of Telecommunications (MINTEL ) and the provincial prefectures. In the info center located in the Guare parish, in Baba canton, province of Los Ríos, the residents of the sector offer training courses in different areas such as computer science, beauty and first aid for people of different ages, who make use of the technology that has that social computing center. All these activities are done for free, being free for all public becomes highly vulnerable and this in turn access the server would run the risk of being attacked, the infocentro is managed by a facilitator, who is the person who is It is in charge of managing the technological resources that the facilities have, as well as controlling the training provided to the community. The facilitator collects the personal data of the people who wish to enroll in the courses that are offered in the place, and this data is stored in the server allowing control of attendance of each student since at the end of the training course each student receives their approval certificate granted by the infocenter. There are many ways to reduce the risks that information is extracted through the network is implementing standards that protect the information.